2018
DOI: 10.1007/s00105-018-4215-5
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus in Deutschland – eine Google-Suchmaschinenanalyse

Abstract: With its unconventional methodology, a Google search engine analysis, this study allows a rough estimation of the medical need of pruritus in the German general population, which seems to be higher than expected. Especially pruritus in the anal area was identified as an unmet medical need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
1
10
0
4
Order By: Relevance
“…Previous studies have shown that Google search analyses are an effective tool for assessing disease trends (38), as well as understanding health information seeking behavior (28,30,32,33). In total, almost 3.5 million Google searches related to skin cancer were observed within 4 years in our study, representing 17.6% of all skin cancer-related Google searches across all of Germany (n = 19,849,230) (30).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Previous studies have shown that Google search analyses are an effective tool for assessing disease trends (38), as well as understanding health information seeking behavior (28,30,32,33). In total, almost 3.5 million Google searches related to skin cancer were observed within 4 years in our study, representing 17.6% of all skin cancer-related Google searches across all of Germany (n = 19,849,230) (30).…”
Section: Discussionmentioning
confidence: 66%
“…A retrospective longitudinal study using Google AdWords Keyword Planner was carried out to identify the search volume of terms related to skin cancer between July 2014 and June 2018 in 9 large cities across Germany (Berlin, Hamburg, Munich, Cologne, Stuttgart, Nuremberg, Muenster, Magdeburg and Recklinghausen). Although Google AdWords Keyword Planner is used primarily to detect keywords for optimizing Google marketing campaigns, this tool can also be used for scientific purposes (30,32,33). The software provides monthly search volume data as estimated by Google.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, analyzing Internet data is useful for examining Internet behavior, interest, and people’s reactions to various incidents [27]. Studies investigating Google search volume data for the term “pruritus” in Germany have demonstrated that this method provides good insight into people’s interests and needs [30,31]. However, dermatological care differs even within Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Dies gilt auch für diejenigen, die sich nicht in ärztlicher Behandlung befinden. Die bisherige Forschung konnte zeigen, dass die Allgemeinbevölkerung häufig Suchmaschinen verwendet, um sich über gesundheitsbezogene Themen zu informieren [11][12][13]. Studien, die speziell die Nutzung von Social-Media-Plattformen als Quelle für gesundheitsbezogene Informationen untersuchen, sind bisher jedoch selten.…”
Section: Introductionunclassified